The Market Efficiency of the Stock Exchange of Mauritius - Sohawon, Devranee (2006)
In the recent years, there has been a lot of focus on the financial systems of the developing countries. Whilst it has been empirically proven that an efficient stock market can contribute towards the economic development of a country, the developing world seems to be lagging behind with the advancement. One of the reasons given was that the developing world is having a lot of trouble catching up with technological innovations and information dissemination. The key to an efficient market is the degree to which information is being disseminated in the market. Developing markets are also illiquid markets and are said to be thin trading.